Effectiveness of Endorphin Massage and Breast Milk Supplements on Lactation Success in Aceh Besar - Yusnaini Yusnaini; Kartinazahri Kartinazahri (Midwifery and Nursing Research, 2023)
Background: The mother's psychological preparation before breastfeeding, stress, excessive worry, unhappiness, all play a major role in the success of exclusive breastfeeding. Endorphin Massage is a light touch and massage that can increase the release of endorphins and oxytocin hormones. If endorphin massage is given to postpartum mothers, it will provide a sense of calm and comfort during lactation so as to increase the response of the posterior pituitary to produce the hormone oxytocin to increase the let down reflex. The purpose of this study was to find out whether there are differences in endorphin massage and breast milk enhancing supplements for lactation success. Methods: This study used a Quasi-Experimental Design method with Pre-test and Posttest with control group design. This research was conducted in Aceh Besar District in 2021. The population in this study were postpartum mothers up to the 3rd day postpartum with a total sample of 51 people. Data analysis used the Anova test and the Post Hoc Test. Results: The results of the ANOVA test showed that there was a difference in LATCH scores between the three groups with a significance value of 0.000